Особенности передачи реалий в авторском переводе романа Владимира Набокова «Лолита» - Полховская, Е.; Георгиади, А.; Анищенко, О. (Культура народов Причерноморья, 2004)
Данное исследование проводилось на материале романа В. Набокова "Лолита" и его авторского перевода на русский язык под одноименным названием. Фактическим материалом послужила сплошная выборка слов, обозначающих национально-специфические реалии, из текстов оригинала и перевода вышеуказанного романа. Дане дослідження проводилося на матеріалі романа В. Набокова "Лоліта" і його авторського перекладу на російську мову під однойменною назвою. Фактичним матеріалом послужила суцільна вибірка слів, що позначають національно-специфічні реалії, з текстів оригінала і перекладу вищезгаданого романа. The work was carried out on the material of V. Nabokov's novel "Lolita" and the author's translation of the novel into Russian. The overall analysis of realias from both texts served as the factual material. The choice of the material for study is not accidental as it reflects the modern American life realias. Specific national elements of the national-cultural contents of the texts as well as linguistic means of their expression are the subject of the study.